Time resolution effect on the apparent particle dynamics confined in a nanochannel evaluated by the single particle tracking subject to Brownian motion - Hanasaki, Itsuo; Kazoe, Yutaka; Kitamori, Takehiko (Microfluidics and nanofluidics, 2018)
Experimental observation of fluid dynamics including the diffusion due to the Brownian motion in confined nanospace, e.g., nanochannels and biological cells, and at the interface between the fluid and solid wall in general relies on the tracking of nanoparticles. Combination of finite time resolution with force field between the particle and the wall can cause significant deviation of apparent position distribution and diffusion coefficient from the actual ones. In this article, we show that the exposure time and the frame interval affect the apparent particle dynamics in a nanochannel in different manners. Sufficiently short exposure time enables precise evaluation of the force field with a long frame interval, whereas sufficiently short frame interval is also required in the precise evaluation of the diffusion coefficient. The dependences of the apparent diffusion coefficient and force field on the frame interval with a fixed force field for different particle sizes collapse into a single curve with appropriate nondimensional characterization. These findings are ubiquitously important in the fields of fluid dynamics, chemistry, biology, and their related engineering, where single particle or molecule tracking in the vicinity of solid–fluid interface is the subject of study.